Basic oxygen furnace slag: a sustainable approach to SiO2-Na2O-B2O3-CaO-F glass-ceramic coating production - Ceylan, Iremnur; Karakas, Busra; Ozturk, Gamze; Cicek, Bugra (SPRINGER, 2024)
In this study, basic oxygen furnace slag (BOF) was utilized as a substitute for calcium carbonate (CaCO3) and red iron oxide (Fe2O3) in the production of frit, which serves as the precursor material for glass-ceramics. Two different raw material batches for SiO2-Na2O-B2O3-CaO-F frit were prepared. The batches underwent a melting-quenching process and were classified as frit (F-STD) consisting of 100 wt% commercial raw materials and frit (F-BOF) containing 4.81 wt% BOF slag in its composition. The chemical content, crystalline structure, and thermal behavior of the frits were investigated. F-STD exhibited a T-G of 599.8 degrees C, with corresponding T-C1 and T-C2 values of 642.2 degrees C and 871 degrees C, respectively. F-BOF displayed a T-G of 592.9 degrees C, along with T-C1 and T-C2 values measured at 636.6 degrees C and 861 degrees C. The powdered frits were applied on steel substrates (DC04EK) using the wet spray method and subsequently heat-treated at 840 degrees C for 4.5 min to obtain a reference (GC-STD) and partially sustainable (GC-BOF) glass-ceramic coatings. The phase formation, microstructure, adherence, and chemical corrosion resistance of the coatings were compared. The coatings were found to be in the optimum adhesion class, numbered 1, according to the BSI EN10209 standard. Analysis of the GC-STD, with an average bubble size of 29.12 mu m, and GC-BOF, with an average bubble size of 34.2 mu m, revealed fewer and larger diameter bubbles in the sustainable composition. Fluorite (CaF2) and fluorapatite (Ca-5(PO4)(3)F) crystal phases were detected in both samples. The compatibility of BOF slag in glass-ceramic coating formulation was demonstrated by identical characteristics exhibited by GC-STD and GC-BOF.
Keywords: Sustainability; Metallurgical process waste; Slag; Frit; Glass-ceramic coatings; SILICATE GLASS; BOF SLAG; CRYSTALLIZATION; MECHANISM; ENAMEL; INDUSTRIAL; PROPERTY; FLUORINE; SYSTEMS; Materials Science